Evolution of intimate partner violence impacts from cash transfers, food transfers, and behaviour change communication: Mixed-method experimental evidence from a nine-year post-programme follow-up in Bangladesh - Lokot, Michelle; Sultana, Nasrin; Hidrobo, Melissa; Ahmed, Akhter; Hoddinott, John F.; Rakshit, Deboleena; Roy, Shalini; Ranganathan, Meghna (International Food Policy Research Institute, 2024)
Presentation given at SVRI Forum 2024 on October 23, 2024.